Going concern in Companies of Consumer Cyclicals Sector During The Covid-19 Pandemic - Anis Safitri, Anis Safitri; Aisyaturrahmi (International Environmental Conferrence on Biosustainability Advancement, 2024)
The Covid-19 phenomenon has caused a significant decline in financial performance in all sectors, especially the consumer cyclicals sector. The decline in financial performance threatens business continuity in the future. The auditor’s doubts about the company’s survival are shown by giving a going-concern audit opinion. The purpose of this study was to determine the effect of financial distress and KAP’s reputation on acceptance of going concern audit opinions in the consumer cyclicals sector in 2020-2021. The data used in this research is secondary data. The population in this study are consumer cyclicals sector companies that are listed on the Indonesian Stock Exchange in 2020-2021. The data is taken from the company’s annual report. The sample in this study amounted to 102 data selected using purposive sampling method. This study uses logistic regression analysis techniques to prove the hypothesis assisted by SPSS.26 software. The result of this study indicate that the financial distress variable has a significant effect on the acceptance of going concern audit opinions in consumer cyclicals sector companies in 2020- 2021. Meanwhile, the KAP reputation variable has no significant effect on acceptance of going concern audit opinions in consumer cyclicals sector companies in 2020-2021. This research is expected to provide information and understanding to be used as a guide in resolving problems related to going concern. Keywords : Covid-19 Pandemic; Financial Distress; Going Concern Audit Opinion; KAP’s Reputation